BUILDING A MORPHOLOGICAL MODEL FOR DETERMINING HAZARDS IN THE WORKING AND SURROUNDING ENVIRONMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The paper presents a new morphological model for determining occupational and environmental hazards. The modern terminology and the complex of concepts intended for determining a hazardous and safe environment are examined. A classification of hazards is proposed depending on their origin and a morphological model is built. The latter can be used to determine hazards in the working and surrounding environment. Its significance is expressed in the possibility of transforming the ongoing phenomena into the effect of a defined hazard. Occupational and environmental factors in industrial enterprises are systematically presented in the following figures. Each production system operates in the conditions of a specific occupational and surrounding environment and can be represented by a generalised cybernetic scheme. In it, the control object is characterised by a large number of input control disturbing factors and output parameters. Their interaction is characterized by functional and non-functional inputs and outputs, respectively. When defining the hazard, the interaction of production systems with the working and surrounding environment or with other systems is taken as a basis. Presented are System S1 for a production system at an industrial enterprise and S2 for a system of its environment, which can be natural, artificial, urban, other production (human-machine) systems, etc. The environment S2 is safe when the output impact factors (functional and non-functional parameters) created by the production system S1 do not create hazards. The presented morphological model in industrial enterprises reflects a situation represented by the chain ‘phenomenonactioneffect’ described in a tuple. The process of building a morphological model for determining hazards in the occupational and surrounding environment of industrial enterprises goes through the following three stages.The universality of indicated morphological model application is dictated by the consideration of actually existing environmental factors and the transformation of the hazardous phenomenon into a hazardous effect.